DMM Prize 2018 winner: Wenqing Zhou - Monica J. Justice (The Company of Biologists, 2019)
Disease Models & Mechanisms (DMM) is delighted to announce that the winner of the DMM Prize 2018 is Wenqing Zhou, for her paper entitled 'Neutrophil-specific knockout demonstrates a role for mitochondria in regulating neutrophil motility in zebrafish' (Zhou et al., 2018a). The prize of $1000 is awarded to the first author of the paper that is judged by the journal's editors to be the most outstanding contribution to the journal that year. To be considered for the prize, the first author must be a student or a postdoc of no more than 5 years standing.